ESTABLISHMENT OF BAHRI MAMLUKS RULE IN EGYPT - Zukhra Aripova (Galaxy International Interdisciplinary Research Journal, 2022)
In the medieval history of the rule of Egypt, a special place is occupied by the sultans of the Tulunids, Ihshids and Mamluks. In the XIII-XV centuries, Egypt had a special place among the countries of the Middle East due to the activities of the Mamluks. The prestige of the Mamluk sultans increased due to their victories in the fight against the Crusaders and the Mongols in the Middle East. The establishment of Mamluk rule in the history of Egypt, the growth of the superiority of military Mamluks in the country, the rise of the Bakhrit Mamluk sultans (1250-1382) and the political processes of the Burjit (Circassian) Mamluk period (1282-1517) are of particular interest for s this study. This article discusses the historical events associated with the period of the reign of the Mamluks in Egypt in 1250-1517, and the undeniable historical facts that led them to the throne of Egypt.